Performance of millennial lecturers during pandemic Covid-19 - Yohana F. Cahya Palupi Meilani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This study aims to identify the effect of work motivation and work climate, job satisfaction on the performance of millennial lecturers of private Universities LLDIKTI III during pandemic Covid-19. The sudden change in the situation during the Covid-19 pandemic has an impact and unpreparedness in mastering the technology that must be carried out will bring its own stressful situation for lecturers and have an impact on lecturer performance. This study uses quantitative research methods by distributing questionnaires and using purposive sampling technique where the respondent is millenial lecturer and who has worked for at least 2 years, who already have academic level (JJA) minimum Asisten Ahli, lecturer’ certification (serdos), and have worked as permanent lecturers. The research sample collected in this study amounted to 200 respondents with 100% response rate. The statistical analysis method used in this study uses SPSS software. The results of this study are that work motivation has a positive effect on the performance of millennial lecturers, work climate has a positive effect on the performance of millennial lecturers and job satisfaction has a positive effect on the performance of millennial lecturers. The contribution of this research can be used in the field of education, especially for private universities management in improving their milllennial lecturers performance.